If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 = 6y + 24 Reorder the terms: -12 = 24 + 6y Solving -12 = 24 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -12 + -6y = 24 + 6y + -6y Combine like terms: 6y + -6y = 0 -12 + -6y = 24 + 0 -12 + -6y = 24 Add '12' to each side of the equation. -12 + 12 + -6y = 24 + 12 Combine like terms: -12 + 12 = 0 0 + -6y = 24 + 12 -6y = 24 + 12 Combine like terms: 24 + 12 = 36 -6y = 36 Divide each side by '-6'. y = -6 Simplifying y = -6
| x^2+16x+37=0 | | f(x)=0.3(x^2-4x) | | 12x+2x-6y+2y-4x= | | 22=2t+2d | | 360.40-0.06(p)=p | | p^2+8p=25 | | 14-19= | | 360.40-0.06(360.40)=p | | -49-7b=-42 | | 22=2x+2y | | 8=b-1+8 | | q^2-10q-17=0 | | -2.6-11.2= | | -10+10r=80 | | -z+16z-15z+9z=-9 | | 3x-6+3x-6+2x+2+2x+2=142 | | 7x+14=42 | | (130-x)+x=130 | | -6x+x=-2-6(-12x-13) | | (20÷4*2÷5-1)/(-9(-3)-12÷3) | | x^2-43560=0 | | 17j-9j-7j=13 | | m^2+26m-37=0 | | 7c+4c+5c-15c=8 | | 3x+6+2x+4+4x-2=126 | | 20x+13=21x+9 | | p^2-10p-39=0 | | 7s-5s-s=9 | | 4d+7=3d+15 | | C(4,1)*(5/25)*(20/25)^3 | | -3x^2+2xy=0 | | 8p-7p=17 |